Root colonization by arbuscular mycorrhizal fungi is reduced in tomato plants sprayed with fungicides - Okiobe, Simon Thierry; Meidl, Peter; Koths, Timon; Olschewsky, Dustin; Rillig, Matthias C.; Lammel, Daniel R. (Frontiers in Agronomy, 2022)
Arbuscular mycorrhizal fungi (AMF) form symbioses with many agricultural crops and can improve plant biomass and health. The performance of the AM symbiosis is context dependent, for example, usually the inoculation of the AMF Rhizophagus irregularis benefits plant biomass, but benefits can be suppressed by high soil fertility levels. Nevertheless, the importance of many other agricultural management practices on AMF, such as fungicides application, is poorly understood. Also, pesticide regulations usually neglect a comprehensive safety testing of fungicides on AMF and lawmakers require empirical support to improve such laws. The objective of this study was to evaluate the effects of spraying fungicides on tomato plants and the subsequent root colonization of plants grown in natural soil containing AMF and inoculated with R. irregularis. We detected that the inoculation of R. irregularis increased the total root colonization of the control plants that did not receive fungicides and that spraying the plants with the fungicides Signum® and Topas® reduced total root colonization. The effect on specific AM fungal structures was variable according to the product. Signum® reduced the occurrence of arbuscules, while Topas® reduced the occurrence of AM hyphae in the colonized roots. Cuprozin® did not reduce total root colonization but reduced the occurrence of AM vesicles. Sampling time was also relevant. Effects were detected at 90 days, but not at 35 days. Our results show that fungicides safety should be evaluated for their effects on root colonization of crops in non-sterilized soils and at adequate sampling time.